POLA PEMBENTUKAN KALIMAT DENGAN NEGASI DALAM BAHASA SASAK - Lalu Erwan Husnan (Kantor Bahasa Provinsi Maluku Utara, 2019)
Negation is negative form of a sentence. Negation uses negative words which refer to something that was already done or not being done. This writing is aimed at describing the form of negative sentences founded at writing references of Sasak lessons. Therefore, descriptive-qualitative approach is appropriate for this writing. Data are gathered using simak (observing) method which is apllied to mulok text books of 7th, 8th, and 9th class. Data are sentences with negation forms. All lessons (1 up to 16) of each class are taken. Data are analyzed using padan intralingual method using Hubung Banding Menyamakan (HBS) or comparison and hubung banding membedakan (HBB) or differentiate techniques. The method is used to classify the sentences by using the position of the negation marks. The next step is sorting the result into sentences with one or double negation marks with one verb or more. Result shows that negation of Sasak strengthens topicalization system of Sasak by which topic put forward.